The influence of melatonin on the functional state of the human body during desynchronosis - Ablaikhanova, N.T.; Nildibayeva, A.A.; Yessenbekova, А.Y.; Mukhitdin, B.A.; Ussipbek, B.I.; Duissenbek, A.; Kozhamzharova, L.S.; Ydyrys, A. (Fundamental and Experimental Biology, 2024)
In the article the mechanisms of melatonin action in the human body, exploring its impact on circadian rhythms, sleep, the immune system, and overall physiological function were considered. A focal point is the use of melatonin as a pharmacological tool to address dyssynchrony, particularly in students facing new time zones or geographic latitude changes. The study aims to understand melatonin's potential influence on regulating biological rhythms and the general physiological state in such scenarios. It scrutinizes how melatonin affects circadian rhythms, sleep, activity, and overall physiological balance during disruptions in biorhythmic synchronization. Recent studies were analyzed, revealing promising prospects for melatonin in regulating desynchronization and maintaining human health amid altered biological rhythms. Findings indicated that students in the experimental group, who took melatonin, experienced enhanced academic performance, increased work capacity, and improved mood. That underscored melatonin's positive impact on the functional state of the human body, even in the presence of desynchronosis. A study involving 100 students identified changes in circadian rhythms contributing to seasonal depression, with daily melatonin tablets proving effective in alleviating desynchronization symptoms. The article furnishes vital scientific data and practical recommendations, catering to professionals in biomedicine, biology, and pharmacology, as well as individuals keen on understanding human health and biological rhythms.